Multivalued φ-Contractions on Extended b-Metric Spaces - Maria Samreen; Wahid Ullah; Erdal Karapinar (Journal of Function Spaces)
In this paper, we have established some fixed-point results for the class of multivalued φ-contractions in the setting of extended b-metric space. An example is furnished to show the validity of our results. The results we have obtained generalize/extend many recent results by Asl, Bota, Samreen et al., and those contained therein.